(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The main resources for biomass agro-ecotechnologies are cereal straw residues, energy crops and emergent vegetation from wetlands. The herbaceous biomass is a material with low density (20 – 60kg·m-3) therefore new mobile equipment and technologies for biomass communition and densification have to be worked out. The storage, dosage and mixing before compacting is necessary. Because of this we must have a working knowledge of the bulk properties of materials. The angle of repose was investigated of straw, reed and peat particles. It was stated that angle of repose of straw and reed varies between 54 – 55 degrees. Angle of repose of peat particles varies between 40 – 60 degrees. In a bin filled with solid bulk material this material acts on the walls with the horizontal stress. The stress ratio between horizontal and vertical stress is important for equipment design. This ratio was investigated for different size particles of straw, reed and peat. Stress ratio of straw and reed particles varies between 0.6 – 0.7.